2009
DOI: 10.1117/1.3127203
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of fiber-based multiphoton endoscopy with microelectromechanical systems scanning

Abstract: A multiphoton endoscopy system has been developed using a two-axis microelectromechanical systems (MEMS) mirror and double-cladding photonic crystal fiber (DCPCF). The MEMS mirror has a 2-mm-diam, 20-deg optical scanning angle, and 1.26-kHz and 780-Hz resonance frequencies on the x and y axes. The maximum number of resolvable focal spots of the MEMS scanner is 720×720 on the x and y axes, which indicates that the MEMS scanner can potentially support high-resolution multiphoton imaging. The DCPCF is compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 23 publications
0
73
0
Order By: Relevance
“…The development of NLOM probe based on multiphoton excitation that uses a near infrared laser beam for imaging is in progress by several groups [20][21][22]. An important factor that limits the use of NLOM probe in clinical studies is the lack of a compactness and flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of NLOM probe based on multiphoton excitation that uses a near infrared laser beam for imaging is in progress by several groups [20][21][22]. An important factor that limits the use of NLOM probe in clinical studies is the lack of a compactness and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that the technique is compatible with in vivo investigation by the use of a miniaturized NLOM probe, which necessarily uses backscattered imaging. An endoscopic LOM probe is under development by several groups [20][21][22].…”
mentioning
confidence: 99%
“…In the presented area we must consider chromatic dispersion which causes femtosecond pulses to spread to picoseconds pulses when propagating in optical bers, thereby deteriorating the excitation eciency of TPF signals. Tang et al [5] have shown that dispersion of DC PCF broadens the 170 fs pulse to 2.5 ps. Therefore the management of dispersion is a critical issue in the design of TPF endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach compromises co-registration of the two modalities. Other reported approaches have used single Ti-Sapphire broadband femtosecond (fs) laser sources for both spectral domain OCT and multiphoton excited fluorescence imaging systems [25][26][27][28][29][30][31][32]. Double-clad fiber (DCF) can also provide a common path for the two modalities that ensures co-registration.…”
Section: Introductionmentioning
confidence: 99%